DOI: 10.11606/d.38.2021.tde-15042021-152715
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal anatomical description of Isogomphodon oxyrhynchus (Müller & Henle, 1839) and discussion of its phylogenetic position within Carcharhinidae (Chondrichthyes, Carcharhiniformes)

Abstract: The Daggernose shark Isogomphodon oxyrhynchus (Müller & Henle, 1839), sole species in its genus, is endemic to northern South America, from Southern Maranhão State in Brazil to Trinidad and Tobago. Although the species is traditionally classified as estuarine, it occurs also in entirely marine environments. Such habitat shift is seasonal, related to the rain regimen. I. oxyrhynchus is easily recognized by the elongated snout, enlarged pectoral fins and reduced eyes, characteristics which account for its unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Sorenson et al [39] also found that C. porosus and T. obesus are the carcharhinid species that are most similar to C. oxyrhynchus. Although no exclusive similarities were found between C. oxyrhynchus and C. porosus, 26 (58%) of the 45 traits analyzed were highly similar, including the morphology of the lower teeth, which have an elongated crown, with narrow roots in the anterior rows [71]. The distinctive morphology of C. oxyrhynchus does not exclude this species from the genus Carcharhinus, however, given that the tree topology and genetic distances found in the present study emphatically support the inclusion of this species in Carcharhinus.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Sorenson et al [39] also found that C. porosus and T. obesus are the carcharhinid species that are most similar to C. oxyrhynchus. Although no exclusive similarities were found between C. oxyrhynchus and C. porosus, 26 (58%) of the 45 traits analyzed were highly similar, including the morphology of the lower teeth, which have an elongated crown, with narrow roots in the anterior rows [71]. The distinctive morphology of C. oxyrhynchus does not exclude this species from the genus Carcharhinus, however, given that the tree topology and genetic distances found in the present study emphatically support the inclusion of this species in Carcharhinus.…”
Section: Discussionmentioning
confidence: 89%
“…The head and fins are also sexually dimorphic [69], which may be associated with mating behavior patterns [70]. Silva [71] presented an anatomical description of C. oxyrhynchus based on an analysis of skeletal traits, including the dental series and morphology of the neurocranium, mandibular and brachial arches, claspers, fins, and the dermal denticles, which was used for systematic comparisons with other members of the family Carcharhinidae. Silva [71] initially compared C. oxyrhynchus with the fossil species attributed to the genus Isogomphodon, including Isogomphodon acuarius (Probst, 1879), Isogomphodon lerichei (Darterville and Casier, 1943), Isogomphodon gracilis (Jonet, 1966), Isogomphodon caunellensis ( [65]), and Isogomphodon aikenensis (Cicimurri and Knight, 2019), affirming that only the fossil taxa C. aikenensis and C. acuarius should be maintained in Isogomphondon while other taxa were assigned to Carcharhinus.…”
Section: Discussionmentioning
confidence: 99%